Problems of Mangrove Forest Deporestation with the Status of Other User Areas for the Development of Residential Areas and Pond Activities in Kotabaru Regency From A Criminal Perspective - Kity, Kity Tokan; Amin, Muhammad Erham; Syaufi, Ahmad; Mispansyah, Mispansyah (International Journal of Law, Environment, and Natural Resources, 2023)
The purpose of carrying out this journal is to find out that deforestation of mangrove forests in Kotabaru Regency carried out by the community is an environmental crime and they want to know the sanctions that can be imposed on perpetrators of mangrove forest deforestation in Kotabaru Regency which cause damage to the mangrove forest ecosystem. The results of this writing are that the act of deforestation of mangrove forests in Kotabaru Regency, South Kalimantan Province is caused by the local government's RTRWK inventory process being less than thorough because there are still mangrove forests that are included in residential areas and fisheries cultivation areas. Furthermore, the act of mangrove deforestation is a criminal act of environmental destruction because it pollutes and destroys the surrounding environment, destroying mangrove forests, and destroying the mangrove ecosystem. Normative research type, doctrinal legal research type using philosophical thinking by finding a concept, research approach, statutory approach, and conceptual approach. Prescriptive nature of research types and primary secondary and tertiary research. There are still mangrove forest plants based on the author's research which are located on the sea coast of Silver Street, Semayap Village, Kotabaru Regency which extends to the Semayap Village housing complex which is a residential area in the RTRWK Kotabaru Regency is located in a residential area, so the author can conclude that the regional government's inventory process in the RTRW process is not thorough enough and the need for the RTRWK to be revised again, as well as the sea coast area, city boundaries, the village of Stagen District. Kotabaru with the presence of fish and shrimp ponds included in the RTRWK for cultivation areas, the writer can conclude that the regional government inventory process in the RTRW process is not thorough enough and the RTRWK needs to be revised again so that the writer concludes that the local regional government is also responsible for the deportation carried out by residential business actors. and pond cultivation on the side of Silver Street, Semayap Village, Kotabaru Regency up to the Semayap housing complex as well as fish pond cultivation on the coast at the city limits of Stagen Village, Kec. North Sea Island District. new city. The current impact is that this location often floods when the sea water is at high tide. The act of deforestation of mangrove forests in Kotabaru Regency, South Kalimantan Province is an environmental crime. Sanctions that can be imposed on the perpetrators are Article 98 paragraph (1) of the Law of the Republic of Indonesia Number 32 of 2009 concerning Protection and Management of the Environment Article 35 Letter e of the Republic of Indonesia Law Indonesia Number 27 of 2007 concerning Management of Coastal Areas and Small Islands and article 73 letter b of Law of the Republic of Indonesia Number 27 of 2007 concerning Management of Coastal Areas and Small Islands and the regional government should be asked for criminal liability in article 112 and article 113 UUPPLH.